FISCAL STANCE AND MACROECONOMIC PERFORMANCE IN NIGERIA (2012)
Nigeria’s fiscal deficits have persistently exceeded the conventional benchmark of 5.0% as a proportion of Gross Domestic Product (GDP) when it averaged 9.8% per annum between 1970 and 2008. Over the same period, the mean annual growth rates of real GDP, investment and money growth stood at 2.3%, 1.8% and 2.6%, respectively. While, there is a growing body of empirical literature on the effect of fiscal deficit on the current account balance, there is very little attempt by researchers to investigate the extent to which fiscal stance has affected macroeconomic variables in African economies. This study, therefore, examined the impact of fiscal stance on macroeconomic performance in Nigeria covering the period between 1970 and 2008. An open macro-econometric model, based on the standard Keynesian framework, was developed. The model had five major components, namely, output, investment, money supply, inflation, and external sector. This made it possible to evaluate the direct and indirect effects of fiscal stance on real GDP growth, investment, money supply, inflation and exchange rate. A Generalized Method of Moment (GMM) technique was used to estimate the behavioural equations, while Structural Vector Autoregressive (SVAR) technique was employed to determine the impact of fiscal impulse on selected macroeconomic and policy variables. Impulse Response Functions (IRFs) were estimated to ascertain the dynamic responses of the variables to various shocks. This was complemented with the Variance Decompositions (VDCs) to track the proportion of the variations in the dependent variables explained by the independent variables. Both annual and quarterly data were used to estimate the models. Fiscal stance exerted significant positive effects on real GDP growth, investment, money growth and inflation, while the effect on exchange rate was insignificant. A 10.0% increase in fiscal stance increased the real GDP growth, investment, money growth and inflation by 12.1%, 23.4%, 11.9% and 11.1%, respectively, while exchange rate depreciated by 2.4%. A marginal increase of 0.7% in fiscal impulse precipitated money growth, real GDP growth and depreciation of the exchange rate by 0.1%, 0.3% and 0.5%, respectively, while inflation increased by 1.5%. Fiscal impulse, therefore, did not impose significant effects on money growth, real GDP growth and exchange rate, whereas, its effect on inflation was significant. The forecast-error variance in fiscal impulse explained by money growth, inflation, real GDP growth and exchange rate stood at 7.0%, 5.0%, 3.1% and 0.6%, respectively. Innovations in the VDCs of the selected macroeconomic and policy variables were largely explained by their own shocks, except inflation that was strongly determined by fiscal impulse. Fiscal stance as a measure of fiscal policy depreciated the exchange rate and improved the real GDP growth and investment, and raised money supply in Nigeria. The prominence of investment was the main route through which fiscal stance influenced the real sector of the economy. Therefore, fiscal stance of the government should favour investment in order to accelerate economic growth because of its multiplier effects.